If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22y = 7(3y + -4) Reorder the terms: 22y = 7(-4 + 3y) 22y = (-4 * 7 + 3y * 7) 22y = (-28 + 21y) Solving 22y = -28 + 21y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-21y' to each side of the equation. 22y + -21y = -28 + 21y + -21y Combine like terms: 22y + -21y = 1y 1y = -28 + 21y + -21y Combine like terms: 21y + -21y = 0 1y = -28 + 0 1y = -28 Divide each side by '1'. y = -28 Simplifying y = -28
| 4x+3y-3=-15 | | 5y+2-2y=4y+-1 | | 14y=13(y+4) | | -6=3(-2) | | 5(x-5)=110/11 | | 10y^2-2y+3=0 | | 5m+7+4(3m-5)=5(m+5) | | -2-9=5x+6-4x | | 4x+6-3=12 | | x+17=38 | | -2x-2x=19-7 | | 11+3(3y+5)= | | n/2=-4 | | -10y=-90 | | 2x-21=-.8 | | 2x-21=-8 | | 11n=10n+23 | | 6(x+7+8y)= | | (y-9)-(y+4)=6y | | 2x-21=.8 | | 2x-21=.08 | | 10x+2=8x+22 | | 2x/(x+4)=5 | | 2r^3+16r^2=40r | | 0.5(2(-15)-4)=-17 | | P=80-2P | | 6x-15-x=6x-13 | | (4-x)+2=9 | | 6p-(5p+5)=8-2(p+12) | | 7(3+c)=6(c-5) | | z^2-3z-108=0 | | 0.4(2(58)+4)=48 |